2021
DOI: 10.1155/2021/4354054
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dahuang Zhechong Pill in Silicosis: A Randomized Controlled Trial

Abstract: Background. There is no effective therapy for silicosis, and Dahuang Zhechong pill (DHZCP), an ancient Chinese medicine prescription, may have a therapeutic effect on silicosis. This study aims to verify the efficacy and safety of DHZCP in silicosis. Methods. This is a randomized controlled clinical trial done at Panzhihua Second People’s Hospital (Panzhihua City, Sichuan Province, China). Participants diagnosed with silicosis were recruited and randomized to the conventional treatment group (CG) or DHZCP comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…Escitalopram was previously the mainstay for the treatment of depression, which is beneficial to improve the symptoms of depression. And alternative medicine (CAM) is often used in order to alleviate these problems [ 5 9 ]. The compound lactic acid bacteria capsule is a drug for the treatment of intestinal flora disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Escitalopram was previously the mainstay for the treatment of depression, which is beneficial to improve the symptoms of depression. And alternative medicine (CAM) is often used in order to alleviate these problems [ 5 9 ]. The compound lactic acid bacteria capsule is a drug for the treatment of intestinal flora disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, herbal compounds have been documented to trigger the generation of ROS, suppress the activation of inflammasomes, and exhibit anti-inflammatory and antifibrotic effects [ 51 ]. Clinical trials have shown that patients' lung function, quality of life, and exercise ability have significantly improved after treatment with traditional Chinese medicines [ 52 ].…”
Section: Treatment For Silicosismentioning
confidence: 99%
“…This shows that tetrandrine combined with acetylcysteine can effectively improve the clinical treatment effect of silicosis and reduce the degree of inflammation in silicosis patients. Tang et al [ 7 ] also found that Dahuang Zhechong pills (DHZCP) could improve lung function, quality of life, and exercise ability in PF patients. The lung damage caused by particulate matter is related to the type and particle size.…”
Section: Introductionmentioning
confidence: 99%